Incorporating novel hierarchical secure model for performance and reliability evaluation in mobile agent system. (21st February 2019) - Mishra, Prashant Kumar; Singh, Raghuraj; Yadav, Vibhash
Emerging mobile agent paradigm supports towards wider applications of mobile agent system (MAS). To guarantee security challenges due to several vulnerable threats into MAS, reliability issues are addressed. In this paper, a hierarchical secure model is designed for reliability prediction of MAS. The proposed security model is categorised as: host security, agent security and communication channel security. Security improvising effects over the reliability enhancements, security is maintained in mobile agent, host and during mobile agent migration. A novel multi-factor authentication is used at mobile agent verification; hosts are verified with respect to the certificate originality and pseudo identity. Opinions from neighbouring host are requested for secure migration of mobile agent. Security-based challenges solved in this paper shows enhancements in reliability of MAS that is estimated in terms of confidentiality, authentication at origin, integrity of agent, quality of mobile agent, security, fault tolerance, dynamic topology and link connectivity. Our proposed MAS are designed in NS3 simulator that results reliability enhancement according to number of mobile agents, size of MAS and number of hosts.